2018
DOI: 10.3389/fmicb.2018.01068
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bacteria and the Characteristics of Actinobacteria Community Structure in Badain Jaran Desert and Tengger Desert of China

Abstract: To assess the diversity of actinobacterial taxa in desert sands and obtain the novel microbial resources, 79 and 50 samples were collected from the Badain Jaran (BJD) and Tengger Deserts (TGD) of China, respectively. High-throughput sequencing (HTS) of environmental 16S rRNA genes within these samples was conducted on an Illumina Miseq platform, using universal bacterial primers targeting the V3–V4 hypervariable region. Based on the HTS analyses, cultivation-dependent (CULD) techniques were optimized to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 38 publications
2
34
3
Order By: Relevance
“…In contrast to our study, Takahashi et al (1996), Okoro et al (2009), and Ding et al (2012) reported highly diverse bacterial communities in desert habitats. In addition, Geodermatophilaceae was only found in the E0 samples (surface soil in the east region) in our study, but it has been reported in the Heihe River Basin of Northwest China (Zhang et al, 2019) and was found to be dominant in both the Tengger and the Badain Jaran deserts in China (Sun et al, 2018). Furthermore, Hydrogenophaga was detected in our study, but not in other studies of deserts.…”
Section: Regional Effects On Bacterial Diversitycontrasting
confidence: 87%
“…In contrast to our study, Takahashi et al (1996), Okoro et al (2009), and Ding et al (2012) reported highly diverse bacterial communities in desert habitats. In addition, Geodermatophilaceae was only found in the E0 samples (surface soil in the east region) in our study, but it has been reported in the Heihe River Basin of Northwest China (Zhang et al, 2019) and was found to be dominant in both the Tengger and the Badain Jaran deserts in China (Sun et al, 2018). Furthermore, Hydrogenophaga was detected in our study, but not in other studies of deserts.…”
Section: Regional Effects On Bacterial Diversitycontrasting
confidence: 87%
“…Actinobacteria extend their hyphae growth to promote community stone attachment, Cyanobacteria support the community through photosynthesis, and Proteobacteria aid in the biofilm development (Saiz‐Jimenez et al ., ; Ortega‐Morales et al ., ; Kemmling et al ., ; Kiel and Gaylarde, ; Abdulla, ; Cockell et al ., ). In addition, many of these organisms, particularly Actinobacteria and Cyanobacteria, are tolerant to heavy metals found in the stones, produce pigments to protect from UV light and can survive with minimal nutrient access on stone surfaces (Potts and Friedmann, ; Eppard et al ., ; Scheerer et al ., 2001; Sun et al ., ). These three phyla were more specifically represented in the two‐way cluster analysis and metagenomic bins, which included Rubrobacter , Geodermatophilaceae, Nostocaceae, Chroococcidiospaceae and Sphingomonas .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, many of these organisms, particularly Actinobacteria and Cyanobacteria, are tolerant to heavy metals found in the stones, produce pigments to protect from UV light and can survive with minimal nutrient access on stone surfaces (Potts and Friedmann, 1981;Eppard et al, 1996;Scheerer et al, 2001;Sun et al, 2018). These three phyla were more specifically represented in the twoway cluster analysis and metagenomic bins, which included Rubrobacter, Geodermatophilaceae, Nostocaceae, Chroococcidiospaceae and Sphingomonas.…”
Section: Prominent Microbial Groups Of Stone-dwelling Microbial Commumentioning
confidence: 99%
“…Members of detected phyla, in particular of Actinobacteria and Firmicutes, often prevail in arid environments [46][47][48] due to their ability to resist to UV-radiation and desiccation [49]. Their resistance has been mostly attributed to their ability to produce photoprotective pigments [50] and to repair UVdamages through multiple mechanisms [51].…”
Section: Discussionmentioning
confidence: 99%